2013
DOI: 10.1021/jp309163c
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Smallest Molecular Model of MoS2 Catalyst: S2 Units in the MoSn–/0 (n = 1–5) Clusters

Abstract: Density functional theory (DFT) and coupled cluster theory (CCSD(T)) calculations are carried out to investigate the electronic and structural properties of a series of monomolybdenum sulfide clusters, MoSn(-/0) (n = 1-5). Generalized Koopmans' theorem is applied to predict the vertical detachment energies and simulate the photoelectron spectra (PES). We found that the additional sulfur atoms have a tendency to successively occupy the terminal sites in the sequential sulfidation until the Mo reaches its maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…In particular, partial exchange of terminal disulfides (S 2 2– ) with aqua ligands leads to [Mo 3 S (13‑ x ) (H 2 O) x ] ( x ‑2)+ ( x = 2, 4) which could be identified as the most active catalytic species in solution . Small charged and neutral molybdenum sulfide clusters have also been studied both experimentally and theoretically to understand their catalytic properties. Further insight can also be gained by investigating the surface chemistry of molybdenum sulfide and chemically similar systems, e.g., molybdenum oxides or molybdenum-doped clusters. A series of [MoO­(S 2 ) 2 L 2 ] complexes have been developed by Wu and co-workers as tunable molecular MoS 2 edge-site mimics for electrocatalytic hydrogen production. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, partial exchange of terminal disulfides (S 2 2– ) with aqua ligands leads to [Mo 3 S (13‑ x ) (H 2 O) x ] ( x ‑2)+ ( x = 2, 4) which could be identified as the most active catalytic species in solution . Small charged and neutral molybdenum sulfide clusters have also been studied both experimentally and theoretically to understand their catalytic properties. Further insight can also be gained by investigating the surface chemistry of molybdenum sulfide and chemically similar systems, e.g., molybdenum oxides or molybdenum-doped clusters. A series of [MoO­(S 2 ) 2 L 2 ] complexes have been developed by Wu and co-workers as tunable molecular MoS 2 edge-site mimics for electrocatalytic hydrogen production. …”
Section: Introductionmentioning
confidence: 99%
“…DFT calculations were performed using Gaussian 09 program [34] with the hybrid B3LYP functional [35] (with 20 % Hartree‐Fock exchange). This functional was chosen since it has been widely adopted in previous studies on molybdenum sulfide clusters and provided reasonable results [20a–e] (more discussion on the choice of B3LYP is in the ESI, including the comparison with M06 [36] ). Grimme's dispersion corrections (D3BJ) were included to describe the interactions between atoms more accurately [37] .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Theoretical and experimental studies have revealed that molybdenum sulfide and tungsten sulfide with various coordination states such as MoS 2 edge, MoS 4 2− , Mo 3 S 4 4+ , and Mo 3 S 13 2− exhibit different G H and catalytic ability [68][69][70][71]. Ni and Co are widely applied to MS 2 -derived HER or HDS catalysts because of the enhancement effect rendered by the edge structures [5,46].…”
Section: Msmentioning
confidence: 99%